Fostering interculturality through near-peer role models in Japanese university classroom settings - Egitim, Soyhan; Hooper , Daniel (Journal of International Students, 2026)
This qualitative research examines how near-peer role model (NPRM)-driven intercultural interactions influence the basic psychological needs (BPNs) of both domestic and international students in increasingly diverse Japanese academic environments. The study employs an open-ended survey administered to students enrolled in the same program for 1 year. The data are further supplemented by observation notes to provide additional insights into the effectiveness of these practices. The findings suggest that NPRM-based approaches can effectively enhance students’ integration, engagement, and sense of belonging in multicultural classroom settings. Hence, future research should examine the long-term impact of NPRM-based approaches across diverse academic contexts and how cultural, institutional, and individual factors shape their effectiveness in supporting students’ well-being and academic success.